2020
DOI: 10.1149/1945-7111/ab8c83
|View full text |Cite
|
Sign up to set email alerts
|

Electrode State of Health Estimation for Lithium Ion Batteries Considering Half-cell Potential Change Due to Aging

Abstract: Estimation of electrode state of health (eSOH) is essential to understanding battery degradation status in detail. This is accomplished by considering electrode capacity and a utilization range as eSOH parameters. In this paper, we propose a novel combination of two eSOH estimation approaches (i.e. voltage fitting and differential voltage analysis). By utilizing peak information in the differential voltage curve, the proposed method can separate individual electrode's contributions from the full-cell voltage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…We performed a voltage fitting analysis 44,[52][53][54][55] to confirm that the main failure mode in our cells is the loss of lithium inventory (LLI) over cycle life (Figures S18 and S19). We found that LLI can fully account for the thermodynamic (i.e., C/20) cell capacity loss over life.…”
Section: Lithium Loss Dominates Overall Cell Capacity Loss Over Cyclingmentioning
confidence: 99%
“…We performed a voltage fitting analysis 44,[52][53][54][55] to confirm that the main failure mode in our cells is the loss of lithium inventory (LLI) over cycle life (Figures S18 and S19). We found that LLI can fully account for the thermodynamic (i.e., C/20) cell capacity loss over life.…”
Section: Lithium Loss Dominates Overall Cell Capacity Loss Over Cyclingmentioning
confidence: 99%
“…The electrode state of health is achieved by utilization range as an eSOH parameter and considering electrode capacity. However, the electrode-specific state of health inside a cell has been given less attention [115]. Electrode-specific state of health gives elaborated information on the degradation status of the battery.…”
Section: E Parameter Estimation For Bmsmentioning
confidence: 99%
“…Voltage fitting finds a parameter set with optimized algorithms. The parameter set gives the best fit between measured data and model prediction for the voltage curve [115]. Using a genetic algorithm, a battery model was proposed with electrode parameters by X. Han et al [116], and that was identified by fitting the voltage curve.…”
Section: E Parameter Estimation For Bmsmentioning
confidence: 99%
“…wheret 0 + = t 0 + (c 0 e ) andD e = D e (c 0 e ) with the same boundary conditions as the ones for Eq. (8). Similarly for solving the liquid-phase Ohm's law, Eq.…”
Section: Journal Of the Electrochemical Societymentioning
confidence: 99%
“…For example, it has been shown that without knowledge of the internal state of the cell we could charge the cell blindly with respect to lithium plating, even in cases of moderate capacity fade [2]. To estimate the degradation mechanisms many studies have utilized the voltage [3,4,5,6,2,7], the differential voltage and phase transitions [8]. All these methods require full range voltage data from the open circuit (OC) state or pseudo-OC state, at a very low current rate.…”
mentioning
confidence: 99%